LANGUAGE AND NATIONALISM. BULGARIAN-MACEDONIAN LANGUAGE DISPUTE IN THE CONTEXT OF THE SIGNED TREATY OF GOOD NEIGHBOURSHIP BETWEEN TWO COUNTRIES (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
Theories of nations and nationalism consider language as one ofthe important factors that define the basis of a nation. The languagedispute between Bulgaria and Macedonia is not a recent issue. In its verysharp form it exists since the second half of 19th century when the twoviews were determined: one which embraced a common linguisticstandard for Macedonians and Bulgarians; and the position of the socalled makedonisti, who insisted that a separate linguistic developmentfor Macedonian nation must be introduced. With the codification of theMacedonian linguistic standard in 1944, the language dispute withBulgaria reached another dimension. Following the proclamation of theMacedonian Independence and their recognition by Bulgaria in 1992, anumber of contracts of mutual cooperation remained unsigned due to thelinguistic dispute. A breakthrough was made in 1999 when theDeclaration for Good Neighbourship was signed in Macedonian languagein accordance with the Constitution, and Bulgarian language inaccordance with the Bulgarian Constitution, and a formulation which wasalso accepted when the Treaty of Good Neighbourship was signed in• The purpose of this paper is to use the historical and explicativeapproach to explain the genesis of Bulgarian - Macedonian languagedispute, especially its escalation following the codification of theMacedonian standard language in 1944/1945. Analysis was performedwith the comparative approach, which included analogies with othernational linguistic contexts for the unsustainability of the Bulgarian thesisfor non-existence of an independent Macedonian language. A specialreview was carried out due to the dilemma on whether the formulationfrom the Treaty “Language in accordance to the Constitution” wasBulgaria’s attempt to devalue and deny the autochthony of theMacedonian language as an important marker of the Macedonian nation.